Euglycemia in Diabetic Rats Leads to Reduced Liver Weight via Increased Autophagy and Apoptosis through Increased AMPK and Caspase-3 and Decreased mTOR Activities. (28th April 2015) - Lee, Jun-Ho; Choi, Soo-Bong; Jin, Mingli; Lee, Ju-Han; Han, Sang-Don; Bae, Hyemi; Lim, Inja; Noh, Yun-Hee
Abstract : Euglycemia is the ultimate goal in diabetes care to prevent complications. However, the benefits of euglycemia in type 2 diabetes are controversial because near-euglycemic subjects show higher mortality than moderately hyperglycemic subjects. We previously reported that euglycemic-diabetic rats on calorie-control lose a critical liver weight (LW) compared with hyperglycemic rats. Here, we elucidated the molecular mechanisms underlying the loss of LW in euglycemic-diabetic rats and identified a potential risk in achieving euglycemia by calorie-control. Sprague-Dawley diabetic rats generated by subtotal-pancreatectomy were fed a calorie-controlled diet for 7 weeks to achieve euglycemia using 19 kcal% (19R) or 6 kcal% (6R) protein-containing chow or fed ad libitum (19AL). The diet in both R groups was isocaloric/kg body weight to the sham-operated group (19S). Compared with 19S and hyperglycemic 19AL, both euglycemic R groups showed lower LWs, increased autophagy, and increased AMPK and caspase-3 and decreased mTOR activities. Though degree of insulin deficiency was similar among the diabetic rats, Akt activity was lower, and PTEN activity was higher in both R groups than in 19AL whose signaling patterns were similar to 19S. In conclusion, euglycemia achieved by calorie-control is deleterious in insulin deficiency due to increased autophagy and apoptosis in the liver via AMPK and caspase-3 activation.